Gene expression profiling on pre‐ and post‐erlotinib tumors from patients with head and neck squamous cell carcinoma12. Issue 6 (13th July 2012) - Thomas, Fabienne; Delmar, Paul; Vergez, Sébastien; Rochaix, Philippe; Hennebelle, Isabelle; McLoughlin, Patricia; Benlyazid, Adil; Sarini, Jérôme; Delord, Jean–Pierre
Abstract Background The purpose of our work was to identify genomic predictive markers of erlotinib response in patients with head and neck squamous cell carcinoma (HNSCC). Methods Tumor tissue biopsies were collected before and after treatment for 39 patients. We analyzed genomic expression of the tumors using microarrays to (1) identify genes differentially expressed in baseline samples in patients who were responders vs nonresponders, (2) characterize erlotinib's effect on gene expression, and (3) identify the pharmacodynamic marker of erlotinib. Results Gene expression profiles found no statistically significant differentially expressed genes between responders and nonresponders. An exploratory analysis by combining statistical criteria allowed us to identify genes differentially expressed in nonresponders compared to responders and genes whose expression was modified during erlotinib treatment. Finally, the search of pharmacodynamic markers identified cyclin‐dependent kinase 2‐interacting protein (CINP) as a potential marker of erlotinib efficacy because its expression decreased only in patients who were responders to the treatment. Conclusion This study provides candidate genes potentially involved in erlotinib response in HNSCC. Head Neck, 2012